2009
DOI: 10.1074/jbc.m109.035253
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Neuropeptide Y (NPY) Proteolysis in Blood and Identification of NPY3–35

Abstract: There is little information on how neuropeptide Y (NPY) proteolysis by peptidases occurs in serum, in part because reliable techniques are lacking to distinguish different NPY immunoreactive forms and also because the factors affecting the expression of these enzymes have been poorly studied. In the present study, LC-MS/MS was used to identify and quantify NPY fragments resulting from peptidolytic cleavage of NPY Neuropeptide Y (NPY)2 is a 36-amino acid peptide involved in the central and peripheral control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 47 publications
0
64
0
Order By: Relevance
“…Previous studies have shown that in vitro incubations of NPY in human plasma resulted in cleavage of the COOHterminal amino acid and dipeptide (1,22). We have demonstrated that PYY is significantly degraded to PYY in the pig and also shown that the liver is involved in the COOHterminal truncation (35).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Previous studies have shown that in vitro incubations of NPY in human plasma resulted in cleavage of the COOHterminal amino acid and dipeptide (1,22). We have demonstrated that PYY is significantly degraded to PYY in the pig and also shown that the liver is involved in the COOHterminal truncation (35).…”
Section: Discussionmentioning
confidence: 61%
“…A method for exact measurements of active PYY 3-36 levels (e.g., sandwich ELISA or LC-MS) would therefore be very valuable in the interpretation of the physiological effects of PYY. In vitro degradation of NPY in human plasma has indicated that NPY is COOH terminally cleaved to primarily NPY , and only trace amounts of NPY have been identified (1). As in pig blood and plasma, PYY was COOH terminally degraded in human blood and plasma in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover mass spectrometry has been used to examine peptides without previously understood biological activities (Habermann et al, 2006;Albrethsen et al, 2006b;Aivado et al, 2007). If enzymes are released into, or activated in, the blood and specifically fragment or modify target proteins in a time and dose dependant fashion then these enzyme activities might be assayed using mass spectrometry and pharmacological inhibition (Marshall et al, 2003;Abid et al, 2009;He et al, 2009;Schebb et al, 2009). Biological activities that process blood proteins to release peptides associated with protein regulation might be directly detected by mass spectrometry and independently confirmed by SDS-PAGE and Western blot (Mansfield, 1995;Marshall et al, 2003).…”
Section: F Biological Activitymentioning
confidence: 99%
“…In addition, PK can function as a plasminogen activator, which could contribute to plasminmediated fibrinolysis, activation of metalloproteinases, and adipocyte differentiation [16,17]. Recently, PK has been shown to cleave neuropeptide Y to generate an inactive fragment [18]. Thus, in addition to PK's well-characterized effects in the intrinsic coagulation pathway and the kallikrein kinin system, these recent findings suggest that PK could have a broader array of substrates that could mediate its effects on vascular physiology and metabolism.…”
Section: Introductionmentioning
confidence: 98%